2006
DOI: 10.1002/ijc.21823
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling correlates with treatment response in women with advanced serous epithelial ovarian cancer

Abstract: The majority of epithelial ovarian carcinomas are of serous subtype, with most women presenting at an advanced stage. Approximately 70% respond to initial chemotherapy but eventually relapse. We aimed to find markers of treatment response that might be suitable for routine use, using the gene expression profile of tumor tissue. Thirty one women with histologically-confirmed latestage serous ovarian cancer were classified into 3 groups based on response to treatment (nonresponders, responders with relapse less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Other cell lines were generous gifts from Dr. Nelly Auersperg (University of British Columbia, Vancouver, British Columbia, Canada; IOSE144, IOSE379, and IOSE7576) and Dr. Samuel Mok (Harvard University, Cambridge, MA; HOSE17.1, OVCA420, and OVCA432). Four normal ovarian, 31 serous EOC tissue (22), and 7 EOC RNA (15) samples were described previously. Clinical and pathologic information of EOC patients was obtained from the Royal Brisbane Women's Hospital (Supplementary Table S1).…”
Section: Cell Lines and Ovarian Tissue Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…Other cell lines were generous gifts from Dr. Nelly Auersperg (University of British Columbia, Vancouver, British Columbia, Canada; IOSE144, IOSE379, and IOSE7576) and Dr. Samuel Mok (Harvard University, Cambridge, MA; HOSE17.1, OVCA420, and OVCA432). Four normal ovarian, 31 serous EOC tissue (22), and 7 EOC RNA (15) samples were described previously. Clinical and pathologic information of EOC patients was obtained from the Royal Brisbane Women's Hospital (Supplementary Table S1).…”
Section: Cell Lines and Ovarian Tissue Rnamentioning
confidence: 99%
“…The copy number of KLK7-181 was obtained by subtraction of KLK7-253 from total amplified KLK7. Microarray analysis was performed as previously described (22).…”
Section: Cell Lines and Ovarian Tissue Rnamentioning
confidence: 99%
“…On the contrary, there was more evidence indicating that nuclear over-expression of ID2 in cancer cell could promote tumor progression and was not a favorable prognosis factor in prostate cancer [8], non-small cell lung cancer [19], and ovarian cancer, etc. [20]. In this study, attributing to the similar expression level of ID2 in cytoplasm among NPC, atypical hyperplasia, squamous, and normal nasopharynx tissues, we did not evaluate the correlation of cytoplasm ID2 expression with clinical parameters of NPC patients, whereas in nucleus we found that ID2 over-expression was significantly associated with T classification, N classification, and clinical stages of NPC patients.…”
Section: Discussionmentioning
confidence: 48%
“…27 It has also been demonstrated that decorin expression is proportional to the quantity of tumor stroma; in patients with ovarian cancer, high decorin expression is associated with a higher incidence of relapse. 28 Furthermore, a dominant-negative mutation in U87 cells of the ischemic responsive enzyme "inositolrequiring enzyme 1␣" causes a 48-fold increase in decorin gene expression and is associated with a proinvasive and less angiogenic phenotype. 29 We found that increased levels of decorin gene expression levels were associated with shorter survival.…”
Section: Discussionmentioning
confidence: 99%